2001
DOI: 10.1038/sj.bmt.1703264
|View full text |Cite
|
Sign up to set email alerts
|

Target dose adjustment of busulfan in pediatric patients undergoing bone marrow transplantation

Abstract: Summary:Published data suggest that the average concentration of busulfan at steady state (Bu Css) is critical for successful engraftment in children receiving busulfan as a conditioning agent for bone marrow transplantation (BMT). We previously found in children that a Bu Css Ͻ600 ng/ml correlated with autologous recovery/mixed chimerism; there was no correlation between Bu Css and regimen-related toxicity (RRT). In a cohort continuous with the previous trial, we prospectively evaluated targeted busulfan conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
126
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(128 citation statements)
references
References 11 publications
1
126
1
Order By: Relevance
“…It has been reported that a high steady-state concentration of BU causes toxicities including VOD, 5-10 whereas a low steady-state concentration leads to graft rejection [10][11][12][13][14][15] or relapse/progression of the disease. 11 Targeted dose adjustment of BU to maintain the overall systemic exposure within a proper range may reduce these risks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that a high steady-state concentration of BU causes toxicities including VOD, 5-10 whereas a low steady-state concentration leads to graft rejection [10][11][12][13][14][15] or relapse/progression of the disease. 11 Targeted dose adjustment of BU to maintain the overall systemic exposure within a proper range may reduce these risks.…”
Section: Discussionmentioning
confidence: 99%
“…1 To overcome the disadvantage of oral BU including gastrointestinal absorption, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] i.v. BU was recently introduced into clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…The upper limit of the BU therapeutic range in myeloablative transplantation is usually quoted as a total AUC of 21 600-24 000 mM min (that is, 1350-1500 mM min per dose  16 doses) and the lower limit, 14 400-16 000 mM min (900-1000 mM min per dose  16 doses). 12,31,34,[43][44][45][46] In the RIC regimens used in our study, the upper limits of total AUC were 9600 and 11 600 mM min in the first and second cohorts, respectively, and the lower limit, 6400 and 8400 mM min. The total BU exposure in our patients was only about half of that in patients who received myeloablative conditioning regimens.…”
Section: Discussionmentioning
confidence: 99%
“…31,46 It was estimated in these studies that there would be a graft failure rate of 10-20% if the steady-state concentration of BU dropped below 600 ng/ml (equivalent to an AUC at B900 mM min after an every 6-h dose). In more recent studies that used i.v.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation